Consensus Guidelines for Immunosuppressive Treatment of Dogs with Glomerular Disease Absent a Pathologic Diagnosis. (November 2013) - ,; Pressler, B.; Vaden, S.; Gerber, B.; Langston, C.; Polzin, D.
Abstract : Background: In certain situations, veterinarians must decide whether or not to recommend immunosuppressive therapy for dogs with suspect glomerular disease in the absence of renal biopsy‐derived evidence that active immune mechanisms are contributing to glomerular injury. The purpose of this report is to provide guidelines for the use of immunosuppressive drugs under these conditions. Animals: Animals were not used in this study. Methods: Recommendations were developed by a formal consensus method. Results: Four recommendations were developed and accepted at a high level of consensus (median 92.5% agreement). Renal biopsy should not be performed when contraindications are present or when results will not alter treatment or outcome. Immunosuppressive drugs should not be given when the source of proteinuria is unknown, they are otherwise contraindicated, or a familial nephropathy or amyloidosis is likely. However, they should be considered when dogs are already being given standard therapy and the serum creatinine is >3.0 mg/dL, azotemia is progressive, or hypoalbuminemia is severe. Thorough client communication regarding pros and cons of such treatment as well as close and careful patient monitoring is required. Conclusion and Clinical Importance: These recommendations can help guide the decision about renal biopsy in patients with proteinuria as well as the use of immunosuppressive drugs in those patients where the decision was made not to perform renal biopsy.